Vitamins A and C as radiotherapy adjuncts - literature review of preclinical and clinical evidence - Wiśniowski, Maksymilian; Wiśniowska, Ada; Buczek, Kacper; Kulszo, Katarzyna; Baszun, Bartłomiej; Kozłowska, Aleksandra (Journal of Education, Health and Sport, 2025)
Introduction: Radiotherapy (RT) is a cornerstone in cancer treatment, but its success is often hindered by tumor radioresistance and normal tissue toxicity. Vitamins A and C are being investigated as potential adjuvants to modulate RT outcomes through radiosensitizing, radioprotective, and immune-regulatory mechanisms. Methods and Materials: We reviewed preclinical and clinical studies from PubMed, ScienceDirect, ResearchGate, and Google Scholar using keywords like “radiotherapy”, ”radiation”, “vitamin A”, “vitamin C”, “retinol”, “β-carotene”, “α-carotene”, “β-cryptoxanthin”, “ascorbic acid” and “radiosensitivity”. Results: Vitamin A, particularly all-trans retinoic acid (ATRA), enhances radiosensitivity by promoting immune-mediated tumor regression, impairing DNA repair in cancer stem cells, and reducing radiation-induced normal tissue damage. However, clinical data on β-carotene suggest potential risks, including increased recurrence in some populations (e.g., smokers). Vitamin C shows dose-dependent effects: at physiological levels, it protects normal tissues via antioxidant activity, while at pharmacological intravenous doses, it selectively sensitizes tumors through pro-oxidant mechanisms. Clinical trials indicate potential for mitigating RT toxicity, such as improved xerostomia, but evidence is currently limited. Conclusions: Vitamins A and C may enhance the therapeutic ratio of radiotherapy via distinct biological mechanisms. However, their clinical use requires careful consideration of dose, timing, and patient-specific factors. Further research through well-designed trials is needed to establish optimal protocols and identify which patients are most likely to benefit.